OPTIMIZATION RULES - Olimpia PECINGINA; Constantin BOGDAN; Dragos Vasile VÎGA (Fiabilitate şi Durabilitate)
Nonlinear programming is based on a collection of definitions, theorems, and principles that must be clearly understood if the available nonlinear pro- gramming methods are to be used effectively. This article begins with the definition of the gradient vector, the Hessian matrix, and the various types of extrema (maxima and minima).